Composition of Leaf Essential Oil of Eucalyptus camaldulensis - Ashraf, Muhammad; Ali, Qasim; Anwar, Farooq; Ijaz Hussain, Abdullah (Asian Journal of Chemistry, 2010)
Variation in the yield and chemical composition of essential oil obtained from the leaves of Eucalyptus camaldulensis from saline and non-saline provenances of Pakistan is presented. Eucalyptus camaldulensis leaves contained 0.98 and 0.96 % essential oils from saline and nonsaline areas, respectively. GC-MS analysis of the E. camaldulensis leaves essential oil revealed the presence of 24 and 27 compounds from the saline and non-saline samples, respectively. The principal constituent in the essential oil from saline and non-saline proven-ances was 1,8-cineole 34.42 and 40.05 %, respectively. Other major constituents were: α-pinene (14.68 and 12.43 %), γ-terpinene (9.42 and 7.48 %), ledol (7.42 and 7.67 %) and t-pinocarveol (8.36 and 3.32 %), respectively. Statistical analysis of the data showed that there were no significant differences in the yield of essential oil of E. camaldulensis from saline or non-saline habitats of Pakistan. However, the concentration of most of the chemical components varied significantly (p < 0.05) due to salt stress.